Alumner från SLU, Skogsmästarskolan säger sitt - Vidmark, Jens (SLU/School for Forest Management, 2011)
The purpose of this study is to investigate the forest managers view of the edu-cation at the School for Forest management at SLU and the first years of em-ployment. Surveys were sent to batches 05/08, 06/09 and 07/10 a total of 136 question-naires were sent out. 80 people answered the survey, this gives a response rate of 59 percent The former students rated according to a 9-grade scale how satisfied they were with the different courses they had attended during their years as students at the school. The courses in mathematics and statistics got the highest marks with an average of 7.3, while the entry-level course in law only got an average of 4.6. A major part of the former students had in the questionnaire enquired a leader-ship course and a business course with focus on negotiation techniques during their education. There is a wide variety of employment opportunities for the graduated students. Timber buyers and forest managers or planners are just a few positions that for-mer students now possess. The study shows that there is a big difference in the first introduction to a new work place depending on where the student got hired. The forest planners were the most satisfied while the operation managers thought their introduction left quite a lot more to wish for. The top most important suggestions on how to improve the education at the school are:  Have a united template and way of working among the universities teachers concerning the thesis.  Present a course in business with focus on leadership, negation tech-niques etc.  Integrate more real life exercises in existing courses, have the teachers to follow up the results and give the students feedback on how the tasks were carried out.